Application Development Risk Assessment Model Based on Bayesian Network - Jaka Sembiring; Johan P. Sipayung; Arry A. Arman (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2018)
This paper describes a new risk assessment model for application development and its implementation. The model is developed using a Bayesian network and Boehm’s software risk principles. The Bayesian network is created after mapping top twenty risks in software projects with interrelationship digraph of risk area category. The probability of risk on the network is analyzed and validated using both numerical simulation and subjective probability from several experts in the field and a team of application developers. After obtaining the Bayesian network model, risk exposure is calculated using Boehm's risk principles. Finally, the implementation of the proposed model in a government institution is shown as a real case illustration.